2009
DOI: 10.1002/jcb.22111
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic phosphate modulates responsiveness to 24,25(OH)2D3 in chondrogenic ATDC5 cells

Abstract: Chondrogenic ATDC5 cells were used as a model of in vitro endochondral maturation to study the role of inorganic phosphate (Pi) in the regulation of growth plate chondrocytes by vitamin D3 metabolites. ATDC5 cells that were cultured for 10 days post-confluence in differentiation media and then treated for 24 h with Pi produced a type II collagen matrix based on immunohistochemistry and expressed mRNAs for several chondrocytic markers, including aggrecan, collagen types II and X, cartilage oligomeric matrix pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Very few data are available on how ePP i could regulate gene expression in chondrocytes. In contrast, several evidences support an important role for inorganic phosphate (P i ) as an early differentiation factor in the ATDC5 cell line (43) and other mineralizing cells (44,45). However, mineralizing cells have a high TNAP activity which was not the case of our mature chondrocytes.…”
Section: Discussionmentioning
confidence: 63%
“…Very few data are available on how ePP i could regulate gene expression in chondrocytes. In contrast, several evidences support an important role for inorganic phosphate (P i ) as an early differentiation factor in the ATDC5 cell line (43) and other mineralizing cells (44,45). However, mineralizing cells have a high TNAP activity which was not the case of our mature chondrocytes.…”
Section: Discussionmentioning
confidence: 63%
“…We have also observed Pi-induced apoptosis in ATDC5 cells, a mouse chondrogenic cell line that exhibits a resting zone chondrocyte-like phenotype as evidenced by expression of collagens II and X, Sox9, and cartilage oligomeric matrix protein (COMP) [2,29]. ATDC5 cells respond to 24R,25(OH) 2 D 3 with increased alkaline phosphatase activity and decreased cell number [29].…”
Section: R25(oh) 2 D 3 and Phosphate-induced Apoptosismentioning
confidence: 91%
“…Confluent cultures of HCC38 cells were cultured in the presence of 0.1, 1.0, and 10 M chelerythrine for 24 h, and MTT was measured. In addition, HCC38 cells were treated with 5 and 7.5 mM phosphate to induce apoptosis, as we have previously shown that phosphate induces apoptosis in other cell types (24). We previously showed that tamoxifen, an ER agonist that inhibits PKC, blocks the stimulatory effects of E 2 on proliferation.…”
Section: Methodsmentioning
confidence: 99%